2017
DOI: 10.1097/brs.0000000000001879
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Using Claims Data to Measure Safety of Lumbar Fusion Surgery

Abstract: Study Design Retrospective analysis of patients undergoing elective lumbar fusion operations, comparing rates of repeat spine surgery based on method of ascertainment. Objective We report the accuracy of a claims-based approach for reporting repeat surgery compared to medical records abstraction as the “gold standard.” Summary of Background Information Previous studies have reported the validity of a claims-based algorithm for grouping patients by surgical indication and classifying operative features, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Previous studies have shown high degrees of accuracy when EMR data were validated by manual medical record reviews. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown high degrees of accuracy when EMR data were validated by manual medical record reviews. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Evidence in both the arthroplasty and spine literature is mixed on the accuracy and validity of administrate claims in identifying postoperative complications. [28][29][30][31] Moreover, we do not have patient-specific identifiers or direct clinical information that allows for more complex multivariate regression analysis. Although we were able to match patients by age and sex, there were still differences in comorbidities among the groups which may confound our surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…National population-based databases provide complete information about reoperations without the follow-up loss because the patients had the reoperations in the hospitals in Korea, even after they discharged from the initial hospital after the index operation. The claim-based approach for reporting reoperation was comparably accurate compared with medical records abstraction because the fee-for-service reimbursement system in Korea requires procedure codes of service for every surgical fee 10 . No study has been conducted to evaluate the difference in the reoperation rates between the different lumbar surgical fusion procedures subgroups with the national population database.…”
Section: Discussionmentioning
confidence: 99%